Long-term safety and efficacy of rilpivirine in combination with nucleoside/nucleotide reverse transcriptase inhibitors in HIV-1 infected patients: 336-week rollover study of phase 2b and 3 clinical studies. Issue 6 (November 2021) - Molina, Jean Michel; Ene, Luminita; Cahn, Pedro; Fätkenheuer, Gerd; Van Wijngaerden, Eric; Lombaard, Johan; Zakharova, Natalia; Van Eygen, Veerle; Vanveggel, Simon; Van Solingen-Ristea, Rodica
Background: To evaluate the long-term safety and efficacy of rilpivirine (RPV), a non-nucleoside reverse transcriptase inhibitor (NNRTI), in combination with nucleoside/nucleotide reverse transcriptase inhibitors (NRTIs) in human immunodeficiency virus (HIV)–infected patients. Methods: RPV-treated HIV-infected patients from phase 2b or 3 studies rolled-over into this phase 3, open-label study and received RPV 25 mg once daily (QD) with choice of two NRTIs. Adverse events (AEs), plasma viral load, CD4 + cell count, and antiviral resistance were evaluated. Results: Of the 482 patients treated, 437 (>90%) patients discontinued study treatment; 371 (77%) had switched to commercially available RPV, 14 (2.9%) discontinued due to AEs, and 6 (1.2%) had virologic failure. In this rollover study, patients were followed up to week 336, although data was limited beyond 288 weeks. Forty-five (9.3%) patients were still undergoing treatment at the time of data cut-off for the current analysis (8 February 2018). The most frequently reported AEs were pregnancy in 7 (1.5%) patients and syphilis in 5 (1.0%) patients. Grade 3–4 AEs were reported in 17 (3.5%) patients, and AEs possibly related to RPV in 23 (4.8%) patients. Over 288 weeks of treatment, 80.1% (95% CI: 74.9%; 84.3%) of patients maintained virologic suppression (HIV-1 RNA <50 copies/mL). The absolute CD4 + cell count increased over time until week 192 and remained constant thereafter. Conclusions: RPV 25 mg QD in combination with an investigator-selected background regimen of two NRTIs demonstrated sustained long-term virologic suppression. The treatment was well-tolerated with no new safety findings.